Overview of Monsoon Induced Coastal Erosion Disaster in Peninsular Malaysia Based On Mass-Media Reports - R., Yanalagaran; Noram Irwan, Ramli; Putra Jaya, Ramadhansyah (IOP Publishing, 2019)
Peninsular Malaysia coastline is undergoing extreme level of erosion causing economic retardation and life threatening situation. National Coastal Erosion Studies 1984 shows that around 52% of Peninsular Malaysia’s coastline is undergoing erosion and these value might have increased over the years. Hence, this paper aims to locate the erosion prone area in Peninsular Malaysia in response to monsoon by utilizing documented mass media reports. The review of mass media reports were analysed together with wind speed in representative of monsoon for the five years period to achieve the aim of this paper. The outcome of this study shows that the severity of coastal erosion in Peninsular Malaysia is increasing drastically. In addition, the northeast monsoon shows the highest impact on the erosion disaster especially in the East Coast of Peninsular Malaysia. The result from this empirical studies shows a good correlation between coastal erosion and monsoon in Peninsular Malaysia. Therefore, the coastal erosion is highly catalysed by monsoon (wind) as its prime catalyst.